Features of functioning and directions of development of investment banks in Russia - I. S. Auzin (Путеводитель предпринимателя)
With the help of the development of the banking system around the world, such a term as investment banking was formed. Thus, the current set of banking products and services for the most part does not allow satisfying the existing demand of customers, so banking institutions began to develop at a faster pace. It is the needs of customers that stimulate not only foreign, but also Russian banks to expand the range of services provided, as well as to improve their activities (including in terms of investments).To date for the implementation of the active development of banking services, investment banking is considered as one of the main elements.Now investment banking continues to play one of the most important roles in the process of financing the economic sector. Investment banking is one of the most promising areas of mediation of investment-oriented banks, the main task of which can be attributed to the implementation of investment interests on the part of clients.At the international level, the sphere of investment banking has an important role and place in the economic field. Investment banking is characterized by certain development prospects in the Russian Federation. The practical use of the methods presented in this scientific article can ensure the further development of this area of investment banking in Russia.The subject of research in the article is the economic relations that arise in the process of intermediary activities of investment banks. Research results are to identify relevant aspects of the functioning of investment banks in the Russian Federation. The author substantiated the directions for the development of investment banks in Russia, taking into account the elimination of existing shortcomings.